Methylseleninic Acid Suppresses Breast Cancer Growth via the JAK2/STAT3 Pathway. (June 2019) - Qiu, Changwei; Zhang, Tao; Zhu, Xinying; Qiu, Jinxia; Jiang, Kangfeng; Zhao, Gan; Wu, Haichong; Deng, Ganzhen
Previous studies show that methylseleninic acid (MSA), which is the most common selenium derivative used as a drug in humans, exerts specific cytotoxic effects in several cancer cell types. However, the complex mechanism of these effects has not been fully elucidated. Here, we demonstrate by Cell Counting Kit-8 in mouse breast cancer cell line 4T1 that MSA inhibits cell viability in a concentration-dependent (5, 10, 20 μmol/L) and time-dependent (6, 12, 24 hours) manner. Flow cytometry, Western blot, and Reverse Transcription-Polymerase Chain Reaction (RT-PCR) analyses indicated that MSA inhibits cancer cell invasion and induces apoptosis by the activation of caspase-3, poly ADP ribose polymerase 1 (PARP1), and BCL2-associated X. Furthermore, MSA demonstrated anticancer activity by inhibiting the Janus kinase 2/signal transducers and activators of transcription 3 (JAK2/STAT3) pathway. The MSA treatment for 24 hours decreased the phosphorylation of JAK2 and STAT3 in 4T1 cells by Western blot. We also confirmed this with the use of a JAK2 chemical inhibitor, AG490, as a positive control. In a 4T1 orthotopic allograft model, morphological and TdT-mediated dUTP nick-end labeling analyses showed that MSA treatment (1.5 mg/kg/weight) for 28 days inhibits tumor growth consistent with the clinical anticancer drug cyclophosphamide. Our observations demonstrate that MSA is a potent anticancer drug in breast cancer and uncovered a key role of the JAK2/STAT3 pathway in modulating tumor growth.